2015
DOI: 10.1073/pnas.1500758112
|View full text |Cite
|
Sign up to set email alerts
|

The recent invasion of natural Drosophila simulans populations by the P-element

Abstract: The P-element is one of the best understood eukaryotic transposable elements. It invaded Drosophila melanogaster populations within a few decades but was thought to be absent from close relatives, including Drosophila simulans. Five decades after the spread in D. melanogaster, we provide evidence that the P-element has also invaded D. simulans. P-elements in D. simulans appear to have been acquired recently from D. melanogaster probably via a single horizontal transfer event. Expression data indicate that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(165 citation statements)
references
References 53 publications
8
156
1
Order By: Relevance
“…Depending on the estimator, our observations are consistent with—or modestly lower than—previous estimates of P -element abundance in wild-derived genomes based on in situ hybridization [∼30 copies (Ronsseray et al 1989)], and pooled deep sequencing [∼60 copies (Kofler et al 2015)].…”
Section: Resultssupporting
confidence: 86%
“…Depending on the estimator, our observations are consistent with—or modestly lower than—previous estimates of P -element abundance in wild-derived genomes based on in situ hybridization [∼30 copies (Ronsseray et al 1989)], and pooled deep sequencing [∼60 copies (Kofler et al 2015)].…”
Section: Resultssupporting
confidence: 86%
“…For example, Pool-Seq was used to unravel the genetic basis of complex traits (Bastide et al 2013; Cheeseman et al 2015), identify loci contributing to local adaptation (Lamichhaney et al 2012; Turner et al 2010), trace beneficial loci during experimental evolution (Lang et al 2013; Orozco-terWengel et al 2012; Tobler et al 2014), identify positively selected loci in populations (Bergland et al 2014; Kofler et al 2012; Nolte et al 2012), find genes selected during domestication (Axelsson et al 2013; Rubin et al 2010), study the invasion of transposable elements (Kofler et al 2015a), investigate clonal evolution in cancer (Ding et al 2012), and to identify causative mutations in forward genetic screens (Schneeberger et al 2009). With this rapid gain in popularity, it is important to ensure the reliable analysis of Pool-Seq data.…”
mentioning
confidence: 99%
“…The relative genomic abundance of particular variants can be determined simply by aligning short reads to a consensus sequence for the TE family (Kofler et al 2015a), an approach that could easily be used to compare KP abundance among different wild-derived genotypes. Furthermore, recent technological advancements promise to greatly enhance our ability to examine structural variation at the level of individual TE insertions (Voskoboynik et al 2013;Kim et al 2014;McCoy et al 2014;Berlin et al 2015;Hall et al 2016), which has historically been prevented by the impossibility of assigning most TE-derived sequencing reads to a particular genomic location.…”
Section: Repressor Proteins or Pirnas?mentioning
confidence: 99%
“…Additionally, many P cytotypes must be established by insertions into other piRNA clusters, because a worldwide sampling of P strains revealed that only 50% harbor a P-element insertion in cytological position 1A (Ronsseray et al 1989b). Similarly, the KP structural variant is extremely prevalent in wild-derived genomes (Itoh and Boussy 2002;Itoh et al 2007;Ogura et al 2007;Kofler et al 2015a), however, no single euchromatic P-element insertion (KP or otherwise) is observed to segregate at high frequency (Zhuang et al 2014;Kofler et al 2015b). A plethora of repressor alleles have therefore arisen in D. melanogaster populations since the invasion of the P element.…”
Section: Mutation and Selection In The Rapid Evolution Of Host Represmentioning
confidence: 99%
See 1 more Smart Citation